High-Speed Sharpening and Thermo-activated Refinement of Blade Tools from Synthetic Diamonds - Kundrák, János; Fedorovich, Vladimir; Markopoulos, Angelos P.; Romashov, Dmitry; Pyzhov, Ivan (Manufacturing Technology Journal, 2020)
Processing of synthetic diamonds is accompanied by low productivity and high values of relative con-sumption of diamond wheels. The coefficient of use of diamond grains in these processes does not exceed 5-10%. Using synthetic diamonds as a blade tool, requires sharpening and refinement. This study proposes to use ultra-high-speed machining modes and the same diamond grinding wheel at all stages of tool shaping. At the first stage, i.e. at high speeds, a rough productive sharpening of dia-mond blade tool is made with a wheel on an iron-based binder. At the second stage processing speed is reduced, as a result grains cease to self-sharpen and to wear out. When the iron binder comes into contact with the sharpened diamond, the speed must be increased, so that the temperature in the contact zone of the binder with the rough surface of the cutter, increases. Due to diffusion wear, from the surface of the diamond, the height of the roughness micro-hills decreases. In other words, the process of high-quality thermally activated refinement of the working surface of the diamond cutter starts to be implemented.
Keywords: High-speed Diamond Grinding; Diffusion Wear; Finite Element Method; Tool Sharpening; Surface Rough-ness; Refinement